FEMINISM AND BUREAUCRACY AS A THEORETICAL DISCUSSION (Third Sector Social Economic Review, 2019)
One of the most fundamental case tackled within in the social science and public administration departments is the case of “bureaucracy”. The cases tried to explain in social sciences are evaluated within the specific paradigms as well. The case of “bureaucracy” has been also widely investigated within the several varied paradigms in social science. However it is a missing topic of how the case of bureaucracy is evaluated and discussed by feminist researches. Therefore,  ‘how the feminist researches deal with the case of bureaucracy’ is designated as a research question and it is intended to answer.  In this essay, which is a theoretical discussion study, the question how the case of bureaucracy has been approached  by varied feminist theories is  investigated separately as a historical and theoretical manner and also it is carried out a general evaluation as comparing these theories.
Keywords: Bureaucracy; Feminist Theories; Feminism